Impact of the SARS-CoV-2 nucleocapsid 203K/204R mutations on the inflammatory immune response in COVID-19 severity - Shuaib, Muhammad; Adroub, Sabir; Mourier, Tobias; Mfarrej, Sara; Zhang, Huoming; Esau, Luke; Alsomali, Afrah; Alofi, Fadwa S; Ahmad, Adeel Nazir; Shamsan, Abbas; Khogeer, Asim; Hashem, Anwar M.; et al. (Genome Medicine, 2023)
The excessive inflammatory responses provoked by SARS-CoV-2 infection are critical factors affecting the severity and mortality of COVID-19. Previous work found that two adjacent co-occurring mutations R203K and G204R (KR) on the nucleocapsid (N) protein correlate with increased disease severity in COVID-19 patients. However, links with the host immune response remain unclear. Here, we grouped nasopharyngeal swab samples of COVID-19 patients into two cohorts based on the presence and absence of SARS-CoV-2 nucleocapsid KR mutations. We performed nasopharyngeal transcriptome analysis of age, gender, and ethnicity-matched COVID-19 patients infected with either SARS-CoV-2 with KR mutations in the N protein (KR patients n = 39) or with the wild-type N protein (RG patients n = 39) and compared to healthy controls (n = 34). The impact of KR mutation on immune response was further characterized experimentally by transcriptomic and proteomic profiling of virus-like-particle (VLP) incubated cells. We observed markedly elevated expression of proinflammatory cytokines, chemokines, and interferon-stimulated (ISGs) genes in the KR patients compared to RG patients. Using nasopharyngeal transcriptome data, we found significantly higher levels of neutrophils and neutrophil-to-lymphocyte (NLR) ratio in KR patients than in the RG patients. Furthermore, transcriptomic and proteomic profiling of VLP incubated cells confirmed a similar hyper-inflammatory response mediated by the KR variant. Our data demonstrate an unforeseen connection between nucleocapsid KR mutations and augmented inflammatory immune response in severe COVID-19 patients. These findings provide insights into how mutations in SARS-CoV-2 modulate host immune output and pathogenesis and may contribute to more efficient therapeutics and vaccine development.